2013
DOI: 10.1556/avet.2012.057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic characteristics of small ruminant lentiviruses in Slovenia

Abstract: Small ruminant lentiviruses (SRLV) are spread throughout the world, including Slovenia, where the first evidence of caprine arthritis encephalitis virus (CAEV) infection was found in 1996. This study was conducted to investigate the molecular and genetic characteristics of SRLV infection in Slovenia in order to classify our strains in relation to other known SRLV strains worldwide as well as to establish molecular techniques in concordance with serology. In this study, 340 goats and sheep were tested. Serologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Given that accuracy of ELISAs can be affected by genotype of the infecting virus (Carroza et al 2009, de Andrés et al 2013, it is possible that diagnostic performance may differ between goat populations. However, Polish goats seem to be infected mainly with genotypes A and B (Olech et al unpublished data), which also predominate in other European countries (Kuhar et al 2013, Rachid et al 2013). This fact allows for cautious generalization of obtained results to other European goat populations.…”
Section: Discussionmentioning
confidence: 99%
“…Given that accuracy of ELISAs can be affected by genotype of the infecting virus (Carroza et al 2009, de Andrés et al 2013, it is possible that diagnostic performance may differ between goat populations. However, Polish goats seem to be infected mainly with genotypes A and B (Olech et al unpublished data), which also predominate in other European countries (Kuhar et al 2013, Rachid et al 2013). This fact allows for cautious generalization of obtained results to other European goat populations.…”
Section: Discussionmentioning
confidence: 99%
“…Since the phylogenetic analysis of Slovenian SRLV strains revealed that ovine strains belong to genotype A and caprine strains to genotypes A and B [15,19], two assays were designed for the specific detection of genotype A (MVV assay) and genotype B (CAEV assay) SRLV strains, based mainly on nucleotide sequences from Slovenian strains, as well as nucleotide sequences retrieved from GenBank. Since it is known that SRLV can cross the inter-species barrier [3], it was also designed to differentiate between MVV and CAEV.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples from all animals were taken by jugular venipuncture for both serum and whole blood collection, using 10 ml vacutainers without anticoagulant and 10 ml EDTA vacutainers, respectively. Samples were stored at −20°C until further use, unless peripheral blood leucocytes (PBL) were isolated from whole blood as previously described [19]. Sera samples from the animals investigated were tested for the presence of specific antibodies using a commercial ELISA assay Chekit-CAEV/MVV Screening ELISA Test Kit (IDEXX Laboratories) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations